Downregulation of lncRNA-11496 in the Brain Contributes to Microglia Apoptosis via Regulation of Mef2c in Chronic T. gondii Infection Mice - Sun, Xiahui; Wang, Ting; Wang, Yongliang; Ai, Kang; Pan, Ge; Li, Yan; Zhou, Chunxue; He, Shenyi; Cong, Hua (Frontiers in Molecular Neuroscience, 2020)
Though it is well known that chronic infections of Toxoplasma gondii (T. gondii) can induce mental and behavioral disorders in the host, little is known about the role of long non-coding RNAs (lncRNAs) in this pathological process. In this study, we employed an advanced lncRNAs and mRNAs integration chip (Affymetrix HTA 2.0) to detect the expression of both lncRNAs and mRNAs in T. gondii Chinese 1 strain infected mouse brain. As a result, for the first time, the downregulation of lncRNA-11496 (NONMMUGO11496) was identified as the responsible factor for this pathological process. We showed that dysregulation of lncRNA-11496 affected proliferation, differentiation and apoptosis of mouse microglia. Furthermore, we proved that Mef2c (Myocyte-specific enhancer factor 2C), a member of the MEF2 subfamily, is the target gene of lncRNA-11496. In a more detailed study, we confirmed that lncRNA-11496 positively regulated the expression of Mef2c by binding to histone deacetylase 2 (HDAC2). Importantly, Mef2c itself could coordinate neuronal differentiation, survival, as well as synapse formation. Thus, our current study provides the first evidence in terms of the modulatory action of lncRNAs in chronic toxoplasmosis in T. gondii infected mouse brain, providing a solid scientific basis for using lncRNA-11496 as a therapeutic target to treat T. gondii induced neurological disorder.